The Strategic Role Of Entrepreneurial Financial Literacy, Proactive Seeking Financial Access And Their Impact On SME Performance - Layaman Layaman (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2022)
This research is motivated by the instability in the performance of SMEs caused by business capital problems. Theoretical and empirical studies were carried out to solve the problem, by building three hypotheses. The sample used in this study were 112 SMEs in Cirebon Regency. The analysis technique used is structural equation modeling using AMOS software. The results of the study indicate that entrepreneurial financial literacy has an effect on the SMEs performance, entrepreneurial financial literacy has a weak effect on proactive seeking financial access and proactive seeking financial access has an effect on the SMEs performance. The theoretical and managerial implications are further discussed in this study.